679. Traditional vs. Alternative Agents in Patients with Lower Respiratory Tract Infections Caused by Carbapenem-Resistant Pseudomonas aeruginosa Susceptible to Traditional Agents. (15th December 2022) - Holger, Dana J; Lagnf, Abdalhamid M; Belza, Ana Christine; Alosaimy, Sara; Rebold, Nicholas S; Morrisette, Taylor; Kunz Coyne, Ashlan J; Ghali, Amer El; Veve, Michael P; Rybak, Michael J
Abstract: Background: Comparative effectiveness studies to guide treatment decisions for infections caused by carbapenem-resistant P. aeruginosa (CRPA) susceptible to traditional agents (non-carbapenem β-lactams and fluoroquinolones) are unavailable. This study aims to compare clinical outcomes between patients treated with traditional and alternative treatment regimens for lower respiratory tract infection (LRTI) caused by CRPA that remain susceptible to traditional agents. Methods: Multi-center, retrospective cohort from January 2016 to December 2019. We included adults with CRPA (resistant to ≥ 1 carbapenem; meropenem or imipenem) that were susceptible to ≥1 traditional agent (piperacillin-tazobactam, cefepime, ceftazidime, ciprofloxacin, or aztreonam) by CLSI breakpoints isolated from an LRTI sample. All other antibiotics were considered alternative agents. We excluded patients with known colonization, cystic fibrosis, or who expired ≤24 hours after antibiotic receipt. Primary outcome was 30-day mortality and secondary outcomes included 30-day readmission and 30-day recurrence. Results: In total, 87 patients, 'traditional' treatment (n=53) and 'alternative' treatment (n=34), were included from 2 institutions in Detroit, MI, USA: median(IQR) age 59(20) years, 64.4% male, and 59.8% African American. Median(IQR) APACHE II and Charlson Comorbidity index scores were 24(10) and 4(5), respectively. Most patients received traditional therapy (n=53), most commonly with cefepime (60.4%) or piperacillin-tazobactam (41.5%). While 34(39.0%) were treated with alternative agents, most commonly ceftolozane-tazobactam (64.7%) or an aminoglycoside (29.4%) alone or in combination. Thirty-day mortality was not significantly different between traditional and alternative therapy groups (22.6% and 11.8%), respectively. There was no significant difference between 30-day recurrence (17.0% and 20.6%) or 30-day readmission (22.6% and 17.6%) between groups. Conclusion: Clinical outcomes did not differ significantly between patients receiving traditional vs. alternative agents for LRTI caused by CRPA susceptible to traditional agents. Traditional agents may be considered for these infections. Further comparative studies are needed to guide treatment decisions for CRPA. Disclosures: All Authors : No reported disclosures.